Artificial Intelligence and Signal Processing International Symposium, AISP 2013, Tehran, Iran, December 25-26, 2013, Revised Selected Papers - Movaghar, Ali.; Jamzad, Mansour; Asadi, Hossein; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the International Symposium, on Artificial Intelligence and Signal Processing, AISP 2013, held in Tehran, Iran, in December 2013. The 35 full papers presented were carefully reviewed and selected from 106 submissions. They are organized in topical sections such as image processing, machine vision, medical image processing, signal processing, speech processing, natural language processing, systems and AI applications, robotics.
Image processing -- Machine vision -- Medical image processing -- Signal processing -- Speech processing -- Natural language processing -- Systems and AI applications -- Robotics.
Keywords: Computer science; Artificial intelligence; Image processing; Computer Science; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Electronic books